Evaluation of Antioxidant Capacity and Analysis of Major Phenolic Compounds in Achillea grandifolia by HPLC-DAD with Q-TOF LC/MS Confirmation - (:unkn) unknown (CHIANG MAI UNIV, FAC SCIENCE, 2018)
The aim of this study was to examine for the first time antioxidant properties from ethanol extracts of Achillea grandifolia flowers, leaves and stems using various antioxidant capacity methods. Subsequently, phenolic compounds in the extracts were identified for the first time by ESI-Q-TOF LC/MS and HPLC-DAD methods. The phenolic compounds in A. grandifolia was identified as quercetagetin 3,6-dimethyl ether, quercetin, luteolin-7-O glucoside, rutin, luteolin, caffeic acid, chlorogenic acid, salicylic acid and dicaffeoylquinic acids. Additionally, HPLC-DAD quantification of major phenolic acids and flavonoids was carried out to all of extracts. Compherensive HPLC-DAD-MS analysis showed that flower extract represent the most abundant phenolic compounds. Also, our study clearly demonstrated that the flower showed better antioxidant effects, total phenolic and flavonoid contents than leaf and stem. Therefore, the flower extract could be a rich source of natural antioxidants and is worthy of further studies that may lead to the discovery of new natural antioxidants.
Keywords: phenolic compounds; antioxidant capacity; HPLC-DAD/Q-TOF-MS; A. grandifolia; PERFORMANCE LIQUID-CHROMATOGRAPHY; ESSENTIAL OIL; POWER